Level of Involvement of Preschool Children in Physical Education and Sport - Pilot Research Project "Exercise Right, Stay Healthy" - Vještica, Goran (Sport - nauka i praksa, 2025)
Preschool age is essential for the development of motor skills and the formation of healthy habits. The World Health Organization cautions of the risks of hypokinesia (insufficient physical activity), which can lead to obesity, hypertension, and metabolic diseases. Preschool institutions play an important role in promoting physical activity through organized programs. Research shows that specially designed physical exercise programs improve children's motor abilities, indicating the need for a systemic approach to engaging children in sporting and recreational activities. The project "Exercise Right, Stay Healthy" by the Association for Preschool Sport and Physical Education of Serbia represents one such effort. The subject of this research is parents' perception of the involvement of preschool children in physical education and sport. Accordingly, the main objective of this study is to assess parents' views on their children's participation in physical education and sport. The research was conducted on a sample of 121 parents of children from five Belgrade municipalities (Palilula, Savski Venac, Novi Beograd, Stari Grad, and Voždovac). The results showed that 51.24% of children exercise 1-2 times per week, while 36.36% exercise 3-4 times per week. No statistically significant difference in exercise frequency was observed between boys and girls. Most children possess basic motor skills, such as riding a scooter (76.86%) and a bicycle (39.67%), while activities like swimming (48.76%) and skateboarding (8.26%) are less common. Parents expressed high interest in regularly organized physical exercise in kindergartens, with 95% positive responses. The study emphasized the need for a systemic approach to addressing insufficient physical activity among preschool children.
Keywords: physical education; physical exercise; preschool children; parents